Pharmacoeconomics and its importance in psychiatry - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2010)
The budget for health is limited in Turkey and other developing countries. In order to use the sources as good as possible, for rational drug use, it is necessary to consider economomical outcomes besides efficacy and safety. Most of the research are designed to evaluate pharmacological effect of drugs. Actually, in most of the studies it is necessary to compare economical and clinical data. Pharmacoeconomics focuses on the costs and benefits of the drug therapies. Rational drug use is a planning, conducting and monitoring process which enables effective, safe and affordable pharmacotherapy practice. In simplest words rational use means prescribing the right drug, in adequate dose for the sufficient duration and appropriate to the clinical needs of the patient at lowest cost. Recently because of increases in cost of health services and insufficient budged there is an increasing interest to pharmacoeconomics, which is an interdisiplinary branch. Cost-effectiveness and cost-benefit terms are quite new in the field of psychiatric disease pharmacoeconomics. Medical care for psychiatric patients places an enormous economic and social burden on society. On the basis of available evidence, it is not possible to identify the most cost-effective strategy for the treatment of psychiatric disorders. Beyond doubt from now on it is important to evaluate not only the effectiveness but also economic aspects of the treatment.
Keywords: Rational drug use; pharmacoeconomics; costs; effectiveness; COST-EFFECTIVENESS; SCHIZOPHRENIA; MANAGEMENT